2021
DOI: 10.1101/2021.10.30.466425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of a dsRNA-induced plant immunity pathway by viral movement protein

Abstract: SummaryThe virome of plants is dominated by RNA viruses 1 and several of these cause devastating diseases in cultivated plants leading to global crop losses 2. To infect plants, RNA viruses engage in complex interactions with compatible plant hosts. In cells at the spreading infection front, RNA viruses replicate their genome through double-stranded RNA (dsRNA) intermediates and interact with cellular transport processes to achieve cell-to-cell movement of replicated genome copies through cell wall channels ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…We observed a pattern of SA contents in both self and non-self exDNA treatments, with high amounts at early and late times. In that aspect, many authors have reported that SA peaked minutes after or at 24 h after DAMP sources, similar to our results reported here [ 25 , 32 , 36 , 55 , 57 , 87 ]. Notably, we detected an increase in ABA contents with non-self exDNA treatment at 2 h after treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed a pattern of SA contents in both self and non-self exDNA treatments, with high amounts at early and late times. In that aspect, many authors have reported that SA peaked minutes after or at 24 h after DAMP sources, similar to our results reported here [ 25 , 32 , 36 , 55 , 57 , 87 ]. Notably, we detected an increase in ABA contents with non-self exDNA treatment at 2 h after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Under mechanical damage and after applying 100 µg/mL of self-exDNA, we found a rise in JA levels associated with an oxidative burst; however, non-self exDNA treatment did not affect JA levels. Additionally, JA levels were found with the application of exDNA sources in a similar way to the different reports mentioned [ 25 , 32 , 36 , 55 , 57 , 87 ]. Additionally, we quantified SA and ABA, and four canonical growth regulatory hormones such as Zeatin, Kinetin, iP, and IAA derived from the self and non-self exDNA applications.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation